The Role Of Cognitive Behavioral Therapy In Enhancing Academic Resilience: A Systematic Literature Review - Fau, Sesilianus; Ramli, M.; Hidayah, Nur; Chusniyah, Tutut (Psikopedagogia, 2024)
Academic resilience, the ability of students to achieve success despite facing various challenges, is becoming an increasingly critical aspect of education. Factors such as socio-economic disparities, mental health issues, and academic obstacles can complicate the learning process. Therefore, students' ability to cope with pressure, meet academic demands, overcome difficulties, and adapt to challenges is essential for supporting optimal academic achievement. This systematic review investigates the role of Cognitive Behavioral Therapy (CBT) in enhancing academic resilience by strengthening self-efficacy, addressing socio-economic stressors, and mitigating mental health challenges. Following PRISMA guidelines, the review analyzes 20 peer-reviewed articles published between 2022 and 2024. Data were sourced from PubMed, Scopus, and Web of Science using relevant search terms such as “Cognitive Behavioral Therapy,” “academic resilience,” and “mental health.” CBT has been proven effective in enhancing academic resilience by strengthening coping strategies, improving self-efficacy, and addressing socio-economic and mental health challenges. Its adaptability across diverse cultural contexts and high- pressure fields further reinforces its relevance. By equipping students with psychological skills to manage stress and recover from setbacks, CBT contributes to long-term academic success. Future study should focus on developing culturally responsive CBT programs and conducting longitudinal studies to assess its long-term impact on student success. In the context of guidance and counseling, school counselors can integrate CBT techniques into their services to help students overcome feelings of inadequacy, develop a growth mindset, and manage negative emotions that may affect their academic performance.